Aesthetics in nursing practice as experienced by nurses in Indonesia: A phenomenological study - Feni Betriana; Waraporn Kongsuwan; Rina Mariyana (Belitung Raya Foundation, Indonesia, 2022)
Background: While aesthetics in nursing practice brings out the beauty in nursing, studies regarding how aesthetics are implemented in practice are lacking. Objective: To describe the meanings of aesthetics in nursing practice experienced by nurses in Indonesia. Methods: This qualitative study employed a hermeneutic phenomenological approach based on Gadamerian philosophy. Thirteen nurses were asked to reflect on their experiences of providing aesthetics in their practice through drawing, followed by individual face-to-face interviews. Data were collected in a public hospital in West Sumatra, Indonesia. The interview transcripts and the pictures were analysed following van Manen’s approach. Results: Five thematic categories were revealed: 1) Engaging in caring for persons; 2) Full of compassion; 3) Sympathetic place of care; 4) A joyful time of care; and 5) Distracting the inconvenience in care. Conclusion: Aesthetics in nursing practice is understood and experienced by Indonesian nurses in various ways, not only limited to the visual beauty, cleanness or tidiness of nursing intervention, but are expressed in other ways within caring, including providing care with compassion, applying the art of communication, relieving the pain, and applying innovation in care. These findings can be used to inform nurses in practising aesthetic nursing for enhancing the quality of care.